(untitled) (Proceedings of the International Conference on Education, 2022)
With the development of Internet globalization and the ongoing pandemic, online education has become the mainstream of higher education. While endowed with great convenience and efficiency, virtual education was also doubted of its impact on self-efficacy and academic performance of college students. This study aims to analyze the mediating effect of self-efficacy on the learning outcomes of college students majoring in STEM (science, technology, engineering and mathematics). This is achieved through reviewing mainstream studies on self-efficacy and learning outcomes to descriptively analyze the correlation between them, especially among college STEM students who received online education. Under the theoretical guidance of Bandura’s ternary interaction theory and Self-Determination Theory, our study investigated diverse variables, including the level of self-efficacy and learning outcomes of college STEM students, by a questionnaire with 36 items from existing scales. Through random sampling, a total of 250 college students from 53 universities in 61 cities in China participated in the survey. The primary data were analyzed using linear regression, along with reliability and validity analysis in SPSS. Findings illustrated that college STEM students’ self-efficacy in online learning has a positive and noteworthy impact on learning outcomes. Findings of our study have broad implications for theory and practices. This paper made an effort to provide possible applications and avenues to encourage the overall development of online education in STEM fields by examining self-efficacy in such context. Meantime, it offered recommendations on designing appropriate learning methods to facilitate college students learning motivation and maximize their full potential to improve online learning systems.